Angiotensin converting enzyme inhibitors and angiotensin II receptor blockers and outcomes in patients with COVID-19: a systematic review and meta-analysis. (1st December 2020) - Lo, Kevin Bryan; Bhargav, Ruchika; Salacup, Grace; Pelayo, Jerald; Albano, Jeri; McCullough, Peter A.; Rangaswami, Janani
ABSTRACT: Background: The use of angiotensin-converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) in patients with coronavirus disease 2019 (COVID-19) given their interaction with the angiotensin-converting enzyme-2 (ACE-2) receptor remains controversial. . Objective: To investigate the impact of ACEI/ARB on COVID-19 disease severity and mortality through a systematic review and meta-analysis. Methods: We searched PubMed and CINAHL databases as well as pre-print servers for studies investigating usage of ACEIs/ARBs in patients with COVID-19 compared to a control group of COVID-19 patients without ACEI/ARB use. COVID-19 related severity of disease, and death were identified as end points. Pooled odds ratios (OR) and their 95% confidence intervals (CI) were calculated using random-effects model. Results: 21 studies were included in the meta-analysis. For mortality with ACEI/ARB use, the pooled odds ratio was 1.29 [0.89–1.87] p = 0.18 with heterogeneity of 91%, while the pooled OR for COVID-19 severity was 0.94 [0.59–1.50] p = 0.81 with heterogeneity of 89% (Figure 2). In combining both mortality and severe disease outcomes, the pooled odds ratio was 1.09 [0.80–1.48] p = 0.58 but with heterogeneity of 92%. Expert Opinion: Even on pooled analysis of both un-adjusted data, adjusted data(studies with matched controls) and taking into account factors such as risk of bias of studies via meta regression and sensitivity analyses, the results hold true that ACEI/ARB use is not associated with COVID-19 disease severity or mortality. To look for any potential beneficial effects, randomized controlled trials are needed. Conclusion: use of ACEI/ARB was not associated with increased mortality or severe COVID-19.